Platelet Distribution Width: A Severity Marker Of Pre Eclampsia, Experience At Tertiary Care Hospital - Zahir, Mariam; Sial, Shagufta Saeed; Noreen, Humera (Journal of Rawalpindi Medical College, 2023)
Objectives: To determine mean platelet distribution width in patients with pre-eclampsia. Study design: This is a cross-sectional, descriptive study performed in the Department of Obstetrics and Gynecology, Benazir Bhutto Hospital, Rawalpindi, retrospectively from 01 May 2017 to 01 November 2017 by non-probability consecutive sampling technique. Materials & Methods: A total of 150 pregnant females with mild and severe pre-eclampsia with gestational age > 20 weeks, and an age limit of 18-40 years were included in the study. Patients having deranged coagulation or multiorgan involvement were excluded. Blood and urine samples were collected at the time of presentation. All the blood pressure readings were confirmed by two readings 4-6 hours apart. Mean ± SD was used to express data values. The mean PDW value was calculated for pregnant females with mild and severe preeclampsia. Results: In our study Mean PDW in patients with preeclampsia was 15.86± 0.34. The mean PDW for mild preeclampsia was 15.8± 0.35 and for severe preeclampsia 15.98±0.28.. Conclusion: PDW is a useful marker for the prediction of the severity of preeclampsia before the disease progresses to severe preeclampsia and HELLP. Raised values can help the obstetrician to actively manage the patients in time to reduce maternal and fetal mortality.